ANALYSIS OF CRITICAL DISCOURSE AND RHETORIC SPEECH MINISTER OF EDUCATION NADIEM MAKARIM ON TEACHER'S DAY 2022 AND ITS IMPLEMENTATION IN LEARNING - Dwi, Afria; Goziyah, Goziyah; Syafri, Frimadhona (Universitas Muhammadiyah Tangerang, 2023)
Van Dijk's Critical Discourse Analysis (AWK) on text structure (macro, superstructure, and micro) in the Speech of the Minister of Education Nadiem Makarim on Teacher's Day 2022 is shown by the theme in Nadiem Makarim's speech is an invitation to innovate to realize Independent Learning. The superstructure in the Speech of the Minister of Education Nadiem Makarim on Teacher's Day 2022 consists of a scheme which includes introduction, content and closing; semantics which includes background, detail, and purpose; and presuppositions. The microstructure found in the Speech of the Minister of Education Nadiem Makarim on Teacher's Day 2022 is a graphic lexicon and rhetoric.